Seasonality and Co‐Detection of Respiratory Viral Infections Among Hospitalised Patients Admitted With Acute Respiratory Illness—Valencia Region, Spain, 2010–2021 - Shirreff, George; Chaves, Sandra S.; Coudeville, Laurent; Mengual‐Chuliá, Beatriz; Mira‐Iglesias, Ainara; Puig‐Barberà, Joan; Orrico‐Sanchez, Alejandro; Díez‐Domingo, Javier; Opatowski, Lulla; Lopez‐Labrador, F. Xavier (Influenza and other respiratory viruses, 2024)
ABSTRACT Background Respiratory viruses are known to represent a high burden in winter, yet the seasonality of many viruses remains poorly understood. Better knowledge of co‐circulation and interaction between viruses is critical to prevention and management. We use > 10‐year active surveillance in the Valencia Region to assess seasonality and co‐circulation. Methods Over 2010–2021, samples from patients hospitalised for acute respiratory illness were analysed using multiplex real‐time PCR to test for 9 viruses: influenza, respiratory syncytial virus (RSV), parainfluenza virus (PIV), rhino/enteroviruses (HRV/ENV), metapneumovirus (MPV), bocavirus, adenovirus, SARS‐CoV‐2 and non‐SARS coronaviruses (HCoV). Winter seasonal patterns of incidence were examined. Instances of co‐detection of multiple viruses in a sample were analysed and compared with expected values under a crude model of independent circulation. Results Most viruses exhibited consistent patterns between years. Specifically, RSV and influenza seasons were clearly defined, peaking in December–February, as did HCoV and SARS‐CoV‐2. MPV, PIV and HRV/ENV showed less clear seasonality, with circulation outside the observed period. All viruses circulated in January, suggesting any pair had opportunity for co‐infection. Multiple viruses were found in 4% of patients, with more common co‐detection in children under 5 (9%) than older ages. Influenza co‐detection was generally observed infrequently relative to expectation, while RSV co‐detections were more common, particularly among young children. Conclusions We identify characteristic patterns of viruses associated with acute respiratory hospitalisation during winter. Simultaneous circulation permits extensive co‐detection of viruses, particularly in young children. However, virus combinations appear to differ in their rates of co‐detection, meriting further study.